Improving the Properties of Gypsum By Using Additives (Journal of Engineering, 2012)
Gypsum Plaster is an important building materials, and because of the availabilty of its raw materials. In this research the effect of various additives on the properties of plaster was studied , like Polyvinyl Acetate, Furfural, Fumed Silica at different rate of addition and two types of fibers, Carbon Fiber and Polypropylene Fiber to the plaster at a different volumetric rate. It was found that after analysis of the results the use of Furfural as an additive to plaster by 2.5% is the optimum ratio of addition to that it improved the flexural Strength by 3.18%.When using Polyvinyl Acetate it was found that the ratio of the additive 2% is the optimum ratio of addition to the plaster, because it improved the value of the flexural strength by a rate of 3.44% of the value of standards fraction of the mixture of reference. It was noted that the optimum ratio for the addition of Fumed Silica to the plaster is the ratio of 1%, because this ratio of addition increases the flexural strength by 15.26%. For the addition of Carbon Fiber to the plaster it was found that the volumetric ratio of the additive 0.5% is the percentage of perfect accessory after taking into account cost and quality which gives an increase in Flexural Strength by rate of 41.43% .When using Polypropylene Fiber it was found that the optimum percentage ratio of addition 1.5%, where this ratio increases flexural strength by a rate of 23.67% . When using the mixture (PVCF), which contains 2% of Poly vinyl Acetate and 0.5% as a volumetric rate of the carbon fiber to the plaster, increases the value of Flexural Strength by a rate 62.92%. After analyzing the results for all mixtures it was found that the mixture (PVCF) is the best one to satisfy the aim of the research which is to get the best structural properties specially flexural strength for gypsum beams.